Role of Serpine gene polymorphism in recurrent implantation failure and preeclampsia - Nidhi Sharma; Jayashree K Srinivasan; Margeret Harriet Priya; Venkatachalam Sibiya (Wolters Kluwer Medknow Publications, 2017)
This is a rare case of serpine gene polymorphism causing thrombophilia and recurrent implantation failure following intrauterine insemination. SERPINE1 gene encodes plasminogen activator inhibitor type 1 and inhibits fibrinolysis, or clot dissolution. The 4G variant results in increased expression of SERPINE1 and consequently higher inhibition of fibrinolysis, thus leading to thrombophilia. The patient had unexplained primary infertility for 9 years. Ovulation induction was done with gonadotropin releasing hormone (GnRH) agonist long protocol. Recombinant follicle stimulating hormone (FSH) with step down protocol was used. Ovulation trigger was given with recombinant human chorionic gonadotrophin (HCG). Ovum pick up was done after 40 h of trigger. A total of 13 eggs were collected. Patient was put on Cabergoline to prevent ovarian hyperstimulation syndrome (OHSS). Four frozen embryos were transferred on day 14 after Laser-assisted hatching. EmbryoGlue was used to prevent implantation failure. Luteal phase support was given. She was put on enoxaparin and pregnancy has now been confirmed. The patient was on strict monitoring as this gene is also associated with preeclampsia during pregnancy.